TOTALITAS PENDIDIKAN ISLAM DI PONDOK PESANTREN - Firdaus Syah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Pondok Pesantren is an Islamic educational institution that emphasizes Islamic education as a whole, both in the form of concepts and its implementation directly in everyday life. The students live in Islamic boarding schools for a relatively long period of time in order to carry out the learning process. Although religious education is more widely studied, it does not mean that general knowledge is simply forgotten. Many pesantren have now combined their curriculum between the traditional curriculum and the national education curriculum. All santri who live in Islamic boarding schools are bound by rules made by the pesantren caregivers. The regulation applies twenty-four hours a day and night and lasts from the time they start their education at the Islamic boarding school until they are declared graduated. The existence of kyai or pesantren leaders, caregivers, ustadz will determine the continuity of all daily activities of students. The students not only learn formally in the classroom, but all kinds of activities outside the classroom are also used as learning that takes place in a very orderly and orderly manner. By undergoing a total learning process that has been carefully planned in Islamic boarding schools, it is hoped that the students will be able to absorb Islamic education thoroughly and will later become provisions for them when they will enter the real community.